Evaluation, learning and change in research and development organizations: concepts, experiences, and implications for the CGIAR - Horton, Douglas; Galleno, V.; Mackay, Ronald (International Service for National Agricultural Research, 2007)
The Consultative Group for International Agricultural Research (CGIAR) is under strong pressure to enhance its capacity to learn and change. Business as usual is no longer an option in an environment that demands the increasing effectiveness, efficiency and relevance of the services and products provided by its centers. The direction CGIAR centers and the system need to pursue for learning and change will require the right blend of central guidance (e.g. from the Science Council and the Executive Committee) and center-led self-evaluation and change initiatives. Over time, the role of the external bodies and external program and management reviews (EPMR) can become focused on the integrity and quality of internal evaluation and quality assurance systems within individual centers. The success of system governance and management mechanisms will ultimately rest on the degree to which they help build and complement the centers’ own internal evaluation systems and strengthen the capacity of the centers to become learning organizations employing sound self-evaluation and self-improvement practices. Some practical suggestions for strengthening institutional learning and change in the CGIAR are offered.